Architectural Decorations And Ornaments Of Central Asia - M.M. Makhmudova; N.S. Buronov; S.M. Usmanov (Genius Journals, 2024)
This article delves into the rich and intricate history of architectural decorations and ornaments in Central Asia, tracing their evolution from ancient times to the present day. Central Asian architecture is renowned for its elaborate and symbolic ornamentation, which reflects the region's diverse cultural and historical influences. The article provides a comprehensive analysis of the development of these ornaments, detailing the stages of their evolution and the underlying symbolism that has shaped their designs. Through an exploration of various architectural styles and notable examples, the article highlights the unique characteristics and significance of Central Asian ornamentation. Readers will gain insights into the techniques, materials, and artistic traditions that have contributed to the region's distinctive architectural heritage. By uncovering the stories behind these intricate decorations, the article aims to deepen the appreciation of Central Asian architectural art and its enduring legacy.
Keywords: Art; design; local conditions